The theory and evidence behind law enforcement strategies that combat child sexual abuse material - Christensen, Larissa S. (International journal of police science & management, 2021)
This article presents a synthesis of current and innovative law enforcement strategies to combat child sexual abuse material. Six law enforcement strategies were identified through an international literature search and verified by experts via roundtable discussion. Six strategies were identified: public intelligence gathering, polygraph, proactive investigations, risk assessment prioritization, resourced taskforces and collaborative partnerships. Strategies are reported via an adapted version of the ‘EMMIE’ framework: effects, mechanisms, moderators, and implementation considerations. Through applying the adapted framework, this article explains how and why each law enforcement strategy may work, and identifies the factors that may impact each strategy’s success. As a result, this article offers a valuable resource for practice professionals across the globe. The synthesis does not include an assessment of whether prior evidence supports the strategies discussed.